Staff Education and Mothers' Postpartum Feeding Choices in a North Carolina Health Department - Guevara, BethAnn (My University, 2017)
Maternal and pediatric benefits of breastfeeding are extensive, yet national benchmarks for postpartum breastfeeding initiation consistently go unmet nationwide. Evidence suggests that educating healthcare professionals who have contact with pregnant and lactating women can positively affect breastfeeding initiation and duration. This project was set in an eastern North Carolina health department and described 1) change in staff perceptions of and attitudes toward breastfeeding after attending three one-hour education sessions; and 2) change in the percentage of postpartum WIC recipients who chose to breastfeed after staff received breastfeeding education. The primary outcome was shift in self-reported staff perceptions of and attitudes toward breastfeeding as measured by a survey which included the Iowa Infant Feeding Attitudes Scale (IIFAS). The secondary outcome was the percentage of WIC recipients, both before and after staff education sessions, who were breastfeeding at the initial postpartum WIC certification visit. Staff education sessions resulted in no major changes in overall IIFAS scores, though one employee group score was higher. Charts of all patients who presented for postpartum WIC certification visit in the six weeks immediately prior to staff education were reviewed in order to determine baseline breastfeeding percentages. A second group of charts was reviewed for six weeks after staff educational sessions concluded and a slight decrease was noted in both exclusive breastfeeding and combination breast- and formula feeding. In both groups, between 20 and 25% of all charts reviewed showed that mothers had initiated breastfeeding but had stopped before accessing WIC services, revealing an opportunity for effective intervention in the early postpartum period.
N/A
Keywords: breastfeeding, health department, Iowa Infant Feeding Attitude Scale, staff attitude toward breastfeeding, staff perceptions of breastfeeding, WIC